MITIGASI DAN EVAKUASI BENCANA PADA MASA PANDEMI COVID-19 BAGI MASYARAKAT PASIE NAN TIGO KOTO TANGAH KOTA PADANG - Aisyah Elliyanti; Julizar Julizar; Lili Irawati; Miftah Irrahmah; Afriwardi Afriwardi; Yose Ramda Ilhami; Fika Anggraini; Rahmad Syawqi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Disaster events both natural and non-natural factors such as epidemics can occur anytime and anywhere, which can affect communities and individuals. This natural or human-caused event or series of events can result in human casualties and suffering. Losses caused by disasters can be minimized or prevented if people's understanding of the disaster itself is sufficient, especially during the Covid-19 pandemic. Purpose: This activity is to conduct disaster mitigation training in the conditions of the Covid-19 pandemic for teachers at the Kanzul Ulum Islamic Boarding School, Kelurahan, in Pasie Nan Tigo, Koto Tangah District, Padang City. Activity target: the people of Pasie Nan Tigi Koto are able to carry out disaster mitigation and evacuation in the event of an earthquake followed by a tsunami, rising sea levels and waves. Method: activities in the form of lectures and exercises that begin with the distribution of masks to all participants involved in the activity, and filling out questionnaires on Covid-19 prevention and disaster management. After delivering the material, it was followed by a discussion on Covid-19 prevention, as well as drills on disaster mitigation and victim evacuation. The results of the activity were an increase in disaster mitigation and evacuation capabilities as well as an increase in participants' awareness in implementing health protocols for the prevention of Covid-19. Most of the participants' understanding of Covid-19 prevention and disaster management had increased, as evidenced by the increase in the number of correct questionnaire answers during the post-test compared to the pre-test from 50% to 80%. In addition, participants' skills have also increased regarding disaster mitigation, the implementation of evacuation techniques when a disaster occurs and how to evacuate victims when the disaster has subsided. Conclusion: Every individual left behind in a disaster-prone area needs to receive knowledge and training skills in disaster mitigation and evacuation techniques during the Covid-19 pandemic.